The Level of Artificial Intelligence Use and Its Relationship with Social Interaction among the Visually Impaired - حسن, آ.م.د. ئافان عبدالله حسن; عبدالله, م.م. زالە عثمان عبدالله (Sulaimani Journal for Humanities, 2025)
This study aims to determine the level of artificial intelligence (AI) use and the level of social interaction among visually impaired individuals, as well as to examine the relationship between AI use and social interaction. A descriptive correlational methodology was employed. Two instruments were developed by the researchers: a scale for AI use and a scale for social interaction. After confirming the psychometric properties of both instruments, they were administered to a sample of 101 visually impaired individuals (males and females) at the Roshnayee Organization for the Blind in the city of Sulaimani. Data were analyzed using the Wilcoxon test for one sample, the Kolmogorov–Smirnov test, Cronbach’s alpha, and regression analysis. The results indicated that the level of AI use among the visually impaired was low, whereas their level of social interaction was high. Furthermore, a weak positive (direct) correlation was found between AI use and social interaction. Based on these findings, the researchers provided several recommendations and suggestions.
Keywords: artificial intelligence; social interaction; visually impaired